Effect of Artificial Aging Temperature on Mechanical Properties and Micro Structure of Al-Mg-Si Composite - Yono Hadi Pramono; Affandy Subyanto (IPTEK Journal of Proceedings Series, 2018)
Temperature determination used in artificial aging process will affect hardness after quenching process and mechanical properties of Al-Mg-Si composite. Thus, the aim of this research is determining temperature used in aging process to obtain mechanical properties optimum. It was done by the procedures as follows: initially, solution heat treatment of Al-Mg-Si composite was set at 400°C then quenching process on water medium followed by aging treatment at various temperatures (130°C, 180°C, 230°C, 280°C and 330°C) for 1.5 hours of HT. After the process, products were analyzed by hardness test to observe the micro-structure change of the samples. The result shows that hardness value of material increased with temperature process (130-280°C) about 10%. The hardness value rises from 48.05 HV before artificial aging to 53.13 HV.